Effect of Gibberellic Acid and Nutrients on the Growth of Teak in Nursery. I-Poor Performance of Treated Stumps in the Field - Neelay, V. R.; Negi, K. S. (Indian Forester, 1983)
Effect of GA3 Urea, Superphosphate and Rallis tracel on the growth of teak seedlings in nursery and its cODsequent effect after planting the stumps of seedlings in the field was studied. The effect of GA in the nursery bed is positive and enhances the height growth, root growth and vigor of the plan Is if applied alonwith the nutrients, the enhanced growth and vigor of treated sfedlings does not manifest itself in the performance of the stumps, prepared from the treated seedlings for planting in the field. The effect of GA3, is temporary, and the enhanced growth and vigor of seedlings is suspended with the discontinu.tion of treatment. The performance of the stumps in the field conditions exhibit. Inferior quality and growth as compared to the untreated seedlings.